2021
DOI: 10.1007/s00247-021-05111-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of socioeconomic and demographic factors and imaging exam characteristics associated with missed appointments in pediatric radiology

Abstract: Background Missed appointments can have an adverse impact on health outcomes by delaying appropriate imaging, which can be critical in influencing treatment decisions. Objective To assess for socioeconomic and imaging exam factors associated with missed appointments among children scheduled for diagnostic imaging. Materials and methods We retrospectively analyzed children (<18 years) scheduled for outpatient diagnostic imaging during a 12-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…When appointments were scheduled over 21 d in advance, families were 4.07 times more likely to miss their dental appointment. Similar to previous research (Lapidos et al 2016; Flores et al 2021), we found a direct proportion between increased wait days resulting in MCOs. This correlation has implications for administrative workflows and operational effectiveness in dental clinics and organizations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…When appointments were scheduled over 21 d in advance, families were 4.07 times more likely to miss their dental appointment. Similar to previous research (Lapidos et al 2016; Flores et al 2021), we found a direct proportion between increased wait days resulting in MCOs. This correlation has implications for administrative workflows and operational effectiveness in dental clinics and organizations.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, we must acknowledge structural drivers of pediatric health inequities, including how racism has historically contributed to poverty, lack of health care access, and patient mistrust (Boyd 2020). Our findings corroborated the racial/ethnic disparities of MCOs in pediatrics seen in prior studies (da Fonseca and Avenetti 2017; Fischer et al 2017; Lynn et al 2018; Como et al 2019; Flores et al 2021). Identifying factors associated with MCOs of at-risk patient populations allows for programs to be designed to mitigate these barriers, such as interventions addressing psychological, structural, and health literacy barriers (Lapidos et al 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Over a 12-month period, data from the EMR was retrospectively analyzed for 7,275 patients. Patients of the African American race were more likely to miss appointments, with an odds ratio of 1.9 ( 10 ).…”
Section: Race and Ethnicity In No-showsmentioning
confidence: 99%
“…In their original article "Advanced Imaging of Disease Unrelated to the Coronavirus Disease 2019 (COVID-19) during the Pandemic: Effect of Patient Demographics in a Pediatric Emergency Department," Jarret et al probed the important issue that the disparity of imaging resources limits our ability to provide equitable care for all patients regardless of their backgrounds. Shah et al, in the article titled "Racial and Ethnic Disparities in Pediatric Magnetic Resonance Imaging: Missed Care Opportunities," elegantly built on a study of pediatric imaging missed care opportunities (MCOs) by Dr. Efren Flores and his colleagues published in Pediatric Radiology in 2021 [1]. The article by Dr. Shah et al corroborates that pediatric health care providers across specialties must continue to identify systemic barriers to health care access for diverse children and those from socially vulnerable areas.…”
mentioning
confidence: 99%